Zakaz propagowania ustrojów totalitarnych przez nazwy miejsc publicznych — problemy stosowania prawa - Krotoszyński, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
In 2016, the Polish Parliament enacted the Prohibition of the Promotion of Communism Act, which obliged local councils to change the names of public places commemorating communism (or any other totalitarian system) or promoting it otherwise. Based on an extensive review of the rulings of Polish administrative courts, this paper presents two main problems with the application of the law: 1) the problem of the admissibility of the local community’s complaint against the voivode’s decision to rename a public place, and 2) the question on how to decide whether a name promotes communism. Regarding the first one, I suggest that the problem should be solved using the lex superior derogat legi inferiori principle. Regarding the second question, I claim that different assessment methods employed by the courts are understandable due to the ambiguity of the provisions in question and from the perspective of the speech acts theory. However, one can argue that a clear hierarchy of these methods should have been established by the courts.
Keywords: sprawiedliwość tranzycyjna; komemoracja; dekomunizacja; nazwy miejsc publicznych; akty mowy